Social policy review. edited by Tony Maltby, Patricia Kennett and Kirstein Rummery. - Maltby, Tony; Rummery, Kirstein; Kennett, Patricia, 1959- (Policy, 2008)
Social Policy Review provides students, academics and all those interested in welfare issues with critical analyses of progress and change in areas of major interest during the past year. Contributions reflect key themes in the UK and internationally. The first part of the collection focuses on developments and change in core UK social policy areas. Part two provides in-depth analyses of topical issues from both UK and international perspectives, while this year's themed section examines 'Gender and policy'.